A Treatment of the Absorption Spectrum for a Multiphoton 𝑉-Type Three-Level Atom Interacting with a Squeezed Coherent Field in the Presence of Nonlinearities - F. K. Faramawy (Journal of Applied Mathematics)
We study the interaction of a three-level atom with a single mode field through multiphoton transition in a cavity, taking explicitly into account the existence of forms of nonlinearities of both the field and the intensity-dependent atom-field coupling. The analytical forms of the absorption spectrum is calculated using the dressed states of the system. The effects of photon multiplicities, mean photon number, detuning, Kerr-like medium, and the intensity-dependent coupling functional on the absorption spectrum are analyzed.